Walls in Cities: A Conceptual Approach to the Walls of Nicosia - Atun, Resmiye Alpar; Doratli, Naciye (Routledge Journals, Taylor & Francis Ltd, 2009)
Walls play an important role in the spatial configuration of cities. In addition to being one of the main factors or components in the configuration of spatial structure, a wall can also be assigned various intangible social meanings. Multiplicity of walls in many cases especially in partitioned or divided cities, have been studied by many scholars. Nicosia, the capital of the island of Cyprus can best be interpreted with the use of the words: walls, division, buffer zone, green line, destruction, and re-connection. The main aim of this paper is, first, to discuss and interpret the two walls (hard borders) of Nicosia - the historic walls and the buffer zone. Second, the role of these walls with respect to the issue of forming a border will be investigated throughout the partitioning process of the city. Additionally, the paper will try to identify the changing meaning and interpretation of these walls with respect to the two major ethnic communities, who are divided within the city.